2012
DOI: 10.7598/cst2013.284
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Valacyclovir in Pharmaceutical Formulations

Abstract: A simple spectrophotometric method has been developed for the estimation of valacyclovir in pharmaceutical preparations. The method is based on the reaction of the valacyclovir with methanolic solution of para dimethyl amino benzaldehyde (PDAB) in acidic condition producing Schiff base having absorption maximum at 400 nm. Beer's law is obeyed in the concentration of 50-250 µg/mL of valacyclovir. Statistical analysis proves that the proposed method is reproducible and selective for the estimation of valacyclovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Srihari et al [53] developed two simple, sensitive, and economical spectrophotometric methods for the estimation of telmisartan in pharmaceutical dosage forms. A method was based on the formation of chloroform extractable complex of telmisartan with a wool fast blue.…”
Section: Colorimetrymentioning
confidence: 99%
“…Srihari et al [53] developed two simple, sensitive, and economical spectrophotometric methods for the estimation of telmisartan in pharmaceutical dosage forms. A method was based on the formation of chloroform extractable complex of telmisartan with a wool fast blue.…”
Section: Colorimetrymentioning
confidence: 99%
“…It is a nucleoside reverse transcriptase inhibitor with antiretroviral activity against HIV. Review of literature reveals that the drug is estimated by using High Performance Liquid Chromatography [2][3][4][5] and UV-VIS spectroscopy [6][7][8][9][10][11]. The present research describes two simple methods for visible spectrophotometric estimation of Abacavir Sulphate from its tablet Formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Impurity proling and metabolic study of montelukast was reported using mass spectrometric techniques. 12,14 Montelukast sodium is a US pharmacopeia listed drug substance for which six impurities are reported. 13 The impurity identied in the present work is different from the reported impurities.…”
Section: Introductionmentioning
confidence: 99%